Family Size Influence of Students’ Attitude and Performance in Literature- In- English in Public Secondary Schools - C, Olagundoye; R.F., Adebile (Asian Journal of Interdisciplinary Research, 2019)
The study aimed at finding out the family size influence on students’ attitude and performance in Literature - in -English. Self-structured questionnaires were drawn to elicit information from 320 SS2 Students who were randomly selected from 8 secondary schools. The questionnaires were duly completed by the respondents from two local government areas in Ondo State. Only 317 respondents filled their questionnaires completely. The questionnaire comprised two sections. Section A consisted of respondents demographic status which include the name of school, class, sex, family size and position in the family while section B dealt with questionnaire on students’ attitude in literature in English. Data collected were subjected to frequency counts and simple percentage. Findings showed that percentage of students from 1-2 family size was 5.99%, that of 3-4 family size was 38.8% while that of 5-6 family size was 28.8% the family size of 7-8 was 21.6% while the family size of 9-10 was 5.99%. The implication was that the families having 3- 10 children stand the risk of inadequate care in terms of provision of essential academic materials and adequate monitoring which could have influence on the attitude and performance of secondary school students in Literature - in -English.